Targeting Thyrointegrin αvβ3 Using Fluorobenzyl Polyethylene Glycol Conjugated Tetraiodothyroacetic Acid (NP751) in Acute Myeloid Leukemia - Darwish, Noureldien H. E.; Glinsky, Gennadi V.; Sudha, Thangirala; Mousa, Shaker A. (Frontiers in Oncology, 2022)
Background: Acute myeloid leukemia (AML) is associated with poor long-term survival, even with newer therapeutic agents. Here we show the results of our pre-clinical study, in which we evaluate the efficacy of a new thyrointegrin αvβ3 antagonist, named fluorobenzyl Polyethylene glycol conjugated tetraiodothyroacetic acid (fb-PMT). Methods and Results: fb-PMT effectively suppresses the malignant growth of human acute myeloid leukemia (AML) after successful engraftment in transgenic NSG-S xenograft mouse models of either established human AML cell line or primary AML cells. Daily treatment with fb-PMT (1-10 mg/kg body weight) subcutaneously (s.c.) for 3-4 weeks was associated with marked regression of leukemogenesis and extended survival in both models. The efficiency of the fb-PMT therapy was verified using IVIS imaging, flowcytometry and histopathological examination to monitor the engraftment of leukemic cells in the bone marrow and other organs. fb-PMT therapy for 3-4 weeks at 3 and 10 mg/kg daily doses exhibited significant reduction (P<0.0001) of leukemic cell burden of 74% and >95%, respectively. All fb-PMT-treated mice in the 10 mg/kg treatment arm successfully maintained remission after discontinuing the daily treatment. Comprehensive fb-PMT safety assessments demonstrated excellent safety and tolerability at multiple folds above the anticipated human therapeutic doses. Lastly, our genome-wide microarray screens demonstrated that fb-PMT works through the molecular interference mechanism with multiple signaling pathways contributing to growth and survival of leukemic cells. Conclusion: our preclinical findings of the potent anticancer activities of fb-PMT and its favorable safety profiles warrant its clinical investigation for the effective and safe management of AML.